Fancy white trash - Geerling, Marjetta (New York : Viking, 2008)
Fifteen-year-old Abby Savage hopes that her five rules for falling in love will keep her from making the same mistakes as her mother and two older sisters--all unwed mothers who have slept with the same man, among others--while she also tries to help her best friend Cody admit that he is gay, and decide how she really feels about Cody's older brother, Jackson.
Horn Book.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Horn Book, October 2008.
Kliatt, May 2008.
School Library Journal, October 2008.
Keywords: Best friends -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Friendship -- Juvenile fiction; Homosexuality -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Best friends -- Fiction; Family problems -- Fiction; Friendship -- Fiction; Homosexuality -- Fiction; Interpersonal relations -- Fiction; Family life -- Fiction; Friendship -- Fiction; Homosexuality -- Fiction; Interpersonal relations -- Fiction; Arizona -- Juvenile fiction; Arizona -- Fiction; Arizona -- Fiction